How does teacher's style foster students' oral performance in class in the Advanced English I Term II 2013 at the Foreign Language Department of the University of El Salvador? - Tobar Canizalez, Douglas Alejandro
The present study contains five chapters in which investigators have developed their research project. The first chapter deals with the introduction of the study as a whole, in which it is provided the background information of the investigation at hand. Besides that, it contains the aims of it as well as the way in which the necessary data were gathered. Immediately after the introduction of this study, chapter II is presented, which has been divided in three sub chapters as well. In this part, the topics and investigations that were previously done regarding the study at hand are presented. Researchers had to read about the three major academic issues which this study deals with. They selected the information that was of much relevance and help for undertaking this investigation. After reading about the literature, it is showed the information regarding the methodology employed for answering the research question and the three subsidiary questions that investigators postulated. Almost for concluding this step, we have chapter IV, which deals with the analysis of the results of such investigation. Finally, chapter V presents a discussion of the findings that were obtained along this study. After all the chapters that this study has, the conclusions arrived, as well as the recommendations provided after conducting the research.